Differences in incorporation of nucleic acid bases and nucleosides by various Mycoplasma and Acholeplasma species. - McIvor, R S (1978)
Eight species representative of the serological diversity of the Mycoplasmatales were tested for their ability to incorporate radiolabeled nucleic acid precursors into acid-insoluble material. Cultures in complex growth medium were centrifuged and resuspended in minimal essential medium (Eagle). For Acholeplasma laidlawii, labeling occurred mainly during the first 4 h of incubation, with substrate saturation at 20 micron. All organisms tested incorporated uracil, adenine, and guanine; none incorporated cytosine. Thymine was incorporated only by bovine group 7, Mycoplasma putrefaciens, and Mycoplasma pneumoniae (strain 3546), but deoxynucleosides enhanced thymine incorporation in A. laidlawii, Mycoplasma gallisepticum, M. pneumoniae (strain AP-164), and Mycoplasma hyorhinis. Nucleoside incorporation (adenosine, guanosine, uridine, cytidine, and thymidine) was not observed for the arginine-utilizing species, Mycoplasma hominis and Mycoplasma arginini, whereas all other organisms tested incorporated nucleosides. The incorporation pattern provides additional metabolic evidence to support the biochemical and antigenic diversity of these organisms. The recognition of differences in incorporation of nucleic acid precursors is important not only to the specific labeling of these organisms, but also to the study of metabolism and transport.